The Viable but Non-culturable State in Xanthomonas citri subsp. citri is a Reversible State Induced by Low Nutrient Availability and Copper Stress Conditions - Golmohammadi, Morteza; Cubero, Jaime; López, María M.; Llop, Pablo (David Publishing, 2022)
Xcc (Xanthomonas citri subsp. citri) causes citrus bacterial canker, a leaf, stem and fruit spotting disease that affects most commercial citrus species and cultivars. Copper compounds, widely used for management of this pathogen, have been reported as inducers of a VBNC (viable but non-culturable state) in plant pathogenic bacteria. VBNC may be considered as a state preceding bacterial death or as a survival mechanism under adverse conditions. Several experiments were performed to characterize the reversibility and persistence of the VBNC state in Xcc. VBNC was induced in low nutrient medium or with amendment of copper at concentrations used for field disease control. The VBNC condition was demonstrated to persist up to 150 days after copper treatment and was reversed after the addition of culture media without copper or amendment with citrus leaf extract. Xcc viability was evaluated by recovery of colonies on culture media, confirmed by membrane integrity, respiratory activity and by real-time RT-PCR targeting a sequence from the gumD gene. Besides, the colonies recovered were pathogenic on citrus leaves. These results confirm that the VBNC state in Xcc is inducible and reversible and therefore may occur in the phyllosphere when Xcc is under copper stress or starvation.